Impact of Nuclear Factor Erythroid 2–Related Factor 2 in Hepatocellular Carcinoma: Cancer Metabolism and Immune Status - Norifumi Iseda; Shinji Itoh; Tomoharu Yoshizumi; Takahiro Tomiyama; Akinari Morinaga; Kyohei Yugawa; Masahiro Shimokawa; Tomonari Shimagaki; Huanlin Wang; Takeshi Kurihara; Yoshiyuki Kitamura; Yoshihiro Nagao; et al. (Hepatology Communications, 2022)
We examined phosphorylated nuclear factor erythroid 2–related factor 2 (P‐NRF2) expression in surgically resected primary hepatocellular carcinoma (HCC) and investigated the association of P‐NRF2 expression with clinicopathological features and patient outcome. We also evaluated the relationship among NRF2, cancer metabolism, and programmed death ligand 1 (PD‐L1) expression. In this retrospective study, immunohistochemical staining of P‐NRF2 was performed on the samples of 335 patients who underwent hepatic resection for HCC. Tomography/computed tomography using fluorine‐18 fluorodeoxyglucose was performed, and HCC cell lines after NRF2 knockdown were analyzed by array. We also analyzed the expression of PD‐L1 after hypoxia inducible factor 1α (HIF1A) knockdown in NRF2‐overexpressing HCC cell lines. Samples from 121 patients (36.1%) were positive for P‐NRF2. Positive P‐NRF2 expression was significantly associated with high alpha‐fetoprotein (AFP) expression, a high rate of poor differentiation, and microscopic intrahepatic metastasis. In addition, positive P‐NRF2 expression was an independent predictor for recurrence‐free survival and overall survival. NRF2 regulated glucose transporter 1, hexokinase 2, pyruvate kinase isoenzymes L/R, and phosphoglycerate kinase 1 expression and was related to the maximum standardized uptake value. PD‐L1 protein expression levels were increased through hypoxia‐inducible factor 1α after NRF2 overexpression in HCC cells. Conclusions: Our large cohort study revealed that P‐NRF2 expression in cancer cells was associated with clinical outcome in HCC. Additionally, we found that NRF2 was located upstream of cancer metabolism and tumor immunity.